AUTOMATED INFORMATION SYSTEM FOR INVENTORY ACCOUNTING OF A CAR DEPOT WAREHOUSE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper deals with the issues of optimal placement of inventory items in the car depot of the Joint-Stock Company "Uztemiryulyulovchi". The structure of the warehouse is presented, reflecting the main elements of the technological sections, consisting of an unloading section, a cargo reception area, a storage area (temporary and main), a complete set section, and a service and technical room.Monitoring of components and spare parts in the production structures of the car depot performing repair and equipment work is carried out by using information placed in the database of the availability of spare parts, inventory items.The positive aspects of using the database when performing accounting operations with material values are shown. A diagram of the accounting operations of the car depot database has been developed.